2010
DOI: 10.1007/s10571-010-9595-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A as a Crucial Factor in the Sorting of Peptide Hormones to Secretory Granules

Abstract: Chromogranin A (CgA) is a soluble glycoprotein stored along with hormones and neuropeptides in secretory granules of endocrine cells. In the last four decades, intense efforts have been concentrated to characterize the structure and the biological function of CgA. Besides, CgA has been widely used as a diagnostic marker for tumors of endocrine origin, essential hypertension, various inflammatory diseases, and neurodegenerative disorders such as amyotrophic lateral sclerosis and Alzheimer's disease. CgA display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…Chromogranin is a hydrophilic glycoprotein normally released by neuroendocrine cells that, upon proteolysis, produce bioactive peptides with different paracrine, autocrine, and endocrine functions [25]. In the last years, this molecule has been characterized as a promising biomarker for the diagnosis and monitoring of treatment response of gastroenteropancreatic neuroblastic tumors [10].…”
Section: Discussionmentioning
confidence: 99%
“…Chromogranin is a hydrophilic glycoprotein normally released by neuroendocrine cells that, upon proteolysis, produce bioactive peptides with different paracrine, autocrine, and endocrine functions [25]. In the last years, this molecule has been characterized as a promising biomarker for the diagnosis and monitoring of treatment response of gastroenteropancreatic neuroblastic tumors [10].…”
Section: Discussionmentioning
confidence: 99%
“…In the adrenal medulla and most sympathetic postganglionic neurons, dopamine is hydroxylated to norepinephrine. Chromogranin A (CGA) for instance, which is widely used as diagnostic marker for tumors of neuroendocrine origin, seems to have an important role for storage and release of catecholamines (Loh et al, 2004;Elias et al, 2010). Hydroxylation of dopamine to norepinephrine takes place after its active transport into granulated vesicles.…”
Section: Physiology and Pathophysiologymentioning
confidence: 99%
“…Interestingly, Taupenot et al showed that the N‐terminal end of CgA (hCgA 77–115 ) contains an amphipathic α helix (Figure a) that could be necessary, though perhaps not sufficient, for trafficking CgA into the RSP . Secondary structure prediction algorithms revealed the existence of a second α helix in the C‐terminal part of CgA (Figure a), suggesting that this region may also act as a targeting motif . It should be noted that certain processing enzymes, such as prohormone convertases PC1/3, PC2, and PC5/6, are also targeted to SG through α helices present in their C‐terminal part .…”
Section: Chromogranin a Interacts With The Tgn Membrane To Direct Hormentioning
confidence: 99%
“…50 Secondary structure prediction algorithms revealed the existence of a second α helix in the C-terminal part of CgA (Figure 1a), suggesting that this region may also act as a targeting motif. 1 It should be noted that certain processing enzymes, such as prohormone convertases PC1/3, PC2, and PC5/6, are also targeted to SG through α helices present in their C-terminal part. [51][52][53] Moreover, carboxypeptidase E, a prohormone sorting receptor, also interacts with lipid rafts via an amphipathic α helix.…”
Section: Chromogranin a Interacts With The Tgn Membrane To Direct Hmentioning
confidence: 99%
See 1 more Smart Citation